Reprogramming cultured human fungiform (HBO) taste cells into neuron-like cells through in vitro induction - Elkaddi, Nadia; Malik, Bilal; Spielman, Andrew I.; Ozdener, Mehmet Hakan (In vitro cellular & developmental biology. Animal, 2022)
Human taste cells are a heterogeneous population of specialized epithelial cells that are constantly generated from progenitor taste cells. Type I and type III taste cells express some neural markers, and studies have reported that direct innervation by neurons is not required for taste cell development. To our knowledge, no previous study has demonstrated that taste cells can differentiate into neuron-like cells or any other non-taste cell type. Here, for the first time, we describe a simple in vitro method that uses a serum-free neural induction medium to differentiate cultured physiologically functional primary human taste (HBO) cells into neuron-like cells in 2–3 wk with high efficiency. We verified neural attributes of these HBO-derived neuron-like with immunocytochemistry, single-cell calcium imaging, and DiI staining and examined cell morphology using transmission electron microscopy. Induced neuron-like cells demonstrated neuron-specific proteins, dendritic and axonal morphology, and networking behaviors. This technique will open new avenues for translational medicine, autologous cell therapy, regenerative medicine, therapy for neurodegenerative disorders, and drug screening.